High-temperature-resistant silicon carbide electric heating element and preparation method thereof
By mixing silicon carbide powder, fiber, graphite and metallic silicon powder and pressing them into shape, and coating them with mullite precursor sol and composite powder slurry to form a dense coating, the problem of oxidation and corrosion of traditional silicon carbide heating elements at high temperatures is solved, resulting in a longer service life and higher efficiency.
Patent Information
- Application Number
- CN202310843193.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-07-11
AI Technical Summary
Traditional silicon carbide heating elements are prone to oxidation, corrosion, and fatigue damage under high-temperature conditions, affecting their service life and efficiency.
The mixture of silicon carbide powder, silicon carbide fiber, graphite, metallic silicon powder and binder is pressed and molded, coated with a mixture of mullite precursor sol and composite powder slurry, and then calcined to form a dense surface coating. The reaction between yttrium oxide and mullite generates a low-temperature eutectic phase, which enhances the resistance to thermo-oxidative aging.
It improves the resistance to thermo-oxidative aging of silicon carbide heating elements, with small resistivity changes, high flexural strength retention, and low oxidation weight gain, exhibiting good high-temperature resistance.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electric heating elements, in particular to a high-temperature resistant silicon carbide electric heating element and a preparation method thereof. Background Art
[0002] Silicon carbide heating elements are a very common but particularly important high-temperature heating element with the characteristics of good high-temperature stability, strong chemical inertness, low expansion coefficient, and good thermal conductivity. Silicon carbide heating elements are widely used in high-temperature furnaces, electric furnaces, and other industrial heating equipment. Traditional silicon carbide heating elements are prone to oxidation, corrosion, fatigue damage, and other problems under high temperature conditions, which seriously affect the service life and efficiency of the elements. Therefore, studying how to improve the high-temperature performance of silicon carbide heating elements has become the focus of researchers. Due to high temperature conditions, traditional silicon carbide heating elements are prone to oxidation, corrosion, and fatigue damage, which seriously affects the service life and efficiency of the elements. Therefore, new methods and technical means are needed for the research and development of silicon carbide heating elements. Summary of the invention
[0003] The object of the present invention is to provide a high temperature resistant silicon carbide electric heating element and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a high temperature resistant silicon carbide electric heating element and a preparation method thereof, comprising the following steps:
[0005] Step 1: Evenly mix silicon carbide powder, silicon carbide fiber, graphite, metal silicon powder and a binder; press the mixture into a shape to obtain a silicon carbide electric heating element blank; water-cool, biscuit-sinter and roast the blank to obtain a primary product;
[0006] Step 2: Mix water, ethanol and aluminum chloride hexahydrate, add hydrochloric acid to adjust the pH value to 2-3, stir and react in a water bath to obtain aluminum sol; mix ethanol, tetraethyl orthosilicate and water, use hydrochloric acid to adjust the pH value to 2-3, stir and react to obtain silica sol; mix the aluminum sol and silica sol, add 1,2-propylene oxide to obtain a mullite precursor sol;
[0007] Step 3: Dispersing yttrium trioxide powder in anhydrous ethanol, adding sodium dodecylbenzene sulfonate to obtain dispersion A; stirring and dissolving lanthanum nitrate in deionized water, adding cerium nitrate, stirring, and then adding trisodium phosphate solution dropwise while stirring, and continuing to stir to form dispersion B; mixing dispersion A and dispersion B to prepare composite powder;
[0008] Step 4: Mix and stir the composite powder and the mullite precursor sol to obtain a mixed slurry, apply the mixed slurry on the surface of the primary finished product, and calcine at 1200-1500° C. for 3-5 hours to obtain a high-temperature resistant silicon carbide electric heating element.
[0009] Furthermore, in step 1, the amount of each component, by weight percentage, is 70-80% silicon carbide powder, 5-20% silicon carbide fiber, 3-5% graphite, 1-2% metallic silicon powder and 0.5-3% binder.
[0010] Furthermore, in step 1, the water cooling time is 10 to 20 minutes.
[0011] Furthermore, in step 1, the biscuit firing method is performed under vacuum conditions, at a temperature of 800 to 1300° C., and for a time of 15 to 30 minutes.
[0012] Furthermore, in step 1, the calcination temperature is 1500-1800°C.
[0013] Furthermore, in step 2, the molar ratio of tetraethyl orthosilicate, aluminum chloride hexahydrate and 1,2-propylene oxide is (10-14):(2-3):1.
[0014] Furthermore, in step 2, the water bath temperature is 50-65° C., and the stirring reaction time is 1-2 h.
[0015] Furthermore, in step 2, the molar ratio of ethanol, ethyl orthosilicate and water in the silica sol is (3-4):4:(3-4).
[0016] Furthermore, in step 2, the silica sol is stirred for a reaction time of 0.5 to 1 h.
[0017] Furthermore, in step 2, in the mullite precursor sol, the molar ratio of silicon element, aluminum element and 1,2-propylene oxide is 1:3:(6-9).
[0018] Furthermore, in step 3, the amounts of the components in the dispersion A are, by weight, 0.3 to 0.5 parts of yttrium trioxide powder, 10 to 20 parts of anhydrous ethanol, and 0.1 to 0.2 parts of sodium dodecylbenzene sulfonate.
[0019] Furthermore, in step 3, the amounts of the components in dispersion B are, by weight, 2 to 3 parts of lanthanum nitrate, 30 to 40 parts of deionized water, 0.2 to 0.4 parts of cerium nitrate, and 50 to 60 parts of trisodium phosphate solution.
[0020] Furthermore, in step 3, the preparation method of the composite powder is to mix dispersion A and dispersion B in a mass ratio of 1: (1 to 1.5), hydrothermally react at 160 to 200° C. for 18 to 24 hours, wash with ethanol and water several times, dry, and calcine at 400 to 500° C. for 2 to 3 hours to obtain a composite powder.
[0021] Furthermore, in step 4, the mixed slurry contains, by weight percentage, 5 to 10% of the composite powder and 90 to 95% of the mullite precursor sol.
[0022] Furthermore, in step 4, the calcination temperature is 1200-1500° C., and the calcination time is 3-5 hours.
[0023] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention obtains a primary product by mixing silicon carbide powder, silicon carbide fiber, graphite, metallic silicon powder and a binder, and pressing and molding. In order to further improve the product's resistance to thermal oxidative aging, the present invention prepares a mixed slurry and coats it on the surface of the primary product. The coating slurry includes a mullite precursor sol and a composite powder, wherein the mullite precursor sol is prepared with aluminum chloride hexahydrate, tetraethyl orthosilicate and 1,2-propylene oxide as raw materials; the composite powder is prepared with a lanthanum cerate shell layer on the outer layer of yttrium trioxide powder by precipitation method; the mixed slurry is coated on the surface of the primary product, and after calcination, the mullite precursor sol will first generate a mullite layer, which is attached to the surface of the silicon carbide material. As the calcination time increases, the lanthanum cerate shell layer of the composite powder will be due to its poor thermal stability. A large number of cracks gradually appear, releasing the yttrium trioxide inside; at high temperature, yttrium trioxide, as a sintering aid, comes into contact with mullite to further form a low-temperature eutectic phase, which reduces the temperature of liquid phase generation, allowing the liquid phase to participate in the sintering process that was originally dominated by solid-phase reaction. Under the action of the capillary force and surface tension of the liquid phase, the solid phase grains are rearranged, making the surface coating densified, thereby effectively blocking the silicon carbide material from reacting with external oxidizing factors, thereby effectively improving the resistance to thermal oxidation aging.
[0024] In the present invention, the composite powder with a core-shell structure can react with the yttrium oxide in the internal structure of the initial calcination with the mullite precursor sol, thereby effectively ensuring the formation of the mullite layer. It should be supplemented that the amount of the composite powder needs to be controlled at 5 to 10%. When the amount of the composite powder is too high, the content of lanthanum cerate also increases. In the actual application process, the high temperature will cause the lanthanum cerate to continuously split, and a large number of voids will appear in the coating, which will seriously reduce the density of the coating. In the actual use process, oxygen will penetrate into the coating through the voids and directly contact the electric heating element body to cause an oxidation reaction, resulting in performance degradation, shortened service life and other effects. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The raw materials used in the present invention and their sources are as follows: silicon carbide powder comes from Huaian Litai Silicon Carbide Micro Powder Co., Ltd., model 1000#; silicon carbide fiber comes from Saifei Group; graphite comes from Qingdao Tianyuan Graphite Co., Ltd., TS series, with a particle size of 1 to 38 μm; metallic silicon powder comes from Hanxin Zunwei Materials, with a particle size of 45 to 425 μm; the binder is aluminum dihydrogen phosphate; and the concentration of trisodium phosphate is 0.02 mol / L.
[0027] Example 1
[0028] Step 1: 80% silicon carbide powder, 10% silicon carbide fiber, 5% graphite, 2% metal silicon powder and 3% binder are mixed evenly; the mixture is pressed into shape to obtain a silicon carbide electric heating element blank; water-cooled for 10 minutes, biscuit-fired and baked the blank under vacuum, the biscuit temperature is 800°C, the biscuit time is 30 minutes, and baked at 1500°C to obtain a primary finished product;
[0029] Step 2: Mix water, ethanol, and aluminum chloride hexahydrate in a molar ratio of 12:3:1, add hydrochloric acid to adjust the pH value to 2, and stir the reaction at 50°C for 1 hour to obtain aluminum sol; mix ethanol, tetraethyl orthosilicate, and water in a molar ratio of 4:4:3, use hydrochloric acid to adjust the pH value to 2, and stir for 0.5 hour to obtain silica sol; mix aluminum sol, silica sol, and 1,2-propylene oxide to obtain mullite precursor sol; wherein the molar ratio of tetraethyl orthosilicate, aluminum chloride hexahydrate, and 1,2-propylene oxide is 1:3:9;
[0030] Step 3: Disperse 0.4 g of yttrium trioxide powder in 20 g of anhydrous ethanol, add 0.2 g of sodium dodecylbenzene sulfonate to obtain dispersion A; stir and dissolve 2.92 g of lanthanum nitrate (0.009 mol) in 30 g of deionized water, add 0.326 g of cerium nitrate (0.001 mol), stir for 30 min, then add 50 g of trisodium phosphate solution dropwise while stirring, continue stirring for 30 min to form dispersion B; mix dispersion A and dispersion B in a mass ratio of 1:1.5, hydrothermally react at 180°C for 24 h, wash with ethanol and water several times, dry, and calcine at 400°C for 2 h to obtain a composite powder;
[0031] Step 4: Mix and stir 5% composite powder and 95% mullite precursor sol to obtain a mixed slurry, apply the mixed slurry on the surface of the primary finished product with a coating thickness of 5 μm, and calcine at 1200° C. for 3 hours to obtain a high-temperature resistant silicon carbide heating element.
[0032] Example 2
[0033] Step 1: 80% silicon carbide powder, 10% silicon carbide fiber, 5% graphite, 2% metal silicon powder and 3% binder are mixed evenly; the mixture is pressed into shape to obtain a silicon carbide electric heating element blank; water-cooled for 12 minutes, biscuit-fired and baked the blank under vacuum, the biscuit temperature is 900°C, the biscuit time is 20 minutes, and the blank is baked at 1550°C to obtain a primary finished product;
[0034] Step 2: Mix water, ethanol and aluminum chloride hexahydrate in a molar ratio of 12:3:1, add hydrochloric acid to adjust the pH value to 2, and stir the reaction at 55°C for 2 hours to obtain aluminum sol; mix ethanol, tetraethyl orthosilicate and water in a molar ratio of 4:4:3, use hydrochloric acid to adjust the pH value to 2, and stir for 1 hour to obtain silica sol; mix aluminum sol, silica sol and 1,2-propylene oxide to obtain mullite precursor sol; wherein the molar ratio of tetraethyl orthosilicate, aluminum chloride hexahydrate and 1,2-propylene oxide is 1:3:9;
[0035] Step 3: Disperse 0.4 g of yttrium trioxide powder in 20 g of anhydrous ethanol, add 0.2 g of sodium dodecylbenzene sulfonate to obtain dispersion A; stir and dissolve 2.92 g of lanthanum nitrate (0.009 mol) in 30 g of deionized water, add 0.326 g of cerium nitrate (0.001 mol), stir for 40 min, then add 50 g of trisodium phosphate solution dropwise while stirring, continue stirring for 30 min to form dispersion B; mix dispersion A and dispersion B in a mass ratio of 1:1.5, hydrothermally react at 180°C for 24 h, wash with ethanol and water several times, dry, and calcine at 450°C for 2 h to obtain a composite powder;
[0036] Step 4: Mix and stir 5% composite powder and 95% mullite precursor sol to obtain a mixed slurry, apply the mixed slurry on the surface of the primary finished product with a coating thickness of 5 μm, and calcine at 1200° C. for 4 hours to obtain a high-temperature resistant silicon carbide heating element.
[0037] Example 3
[0038] Step 1: 80% silicon carbide powder, 10% silicon carbide fiber, 5% graphite, 2% metal silicon powder and 3% binder are mixed evenly; the mixture is pressed into shape to obtain a silicon carbide electric heating element blank; water-cooled for 20 minutes, biscuit-fired and baked the blank under vacuum conditions, the biscuit temperature is 1000°C, the biscuit time is 20 minutes, and baked at 1600°C to obtain a primary finished product;
[0039] Step 2: Mix water, ethanol, and aluminum chloride hexahydrate in a molar ratio of 12:3:1, add hydrochloric acid to adjust the pH value to 2, and stir the reaction at 65°C for 1 hour to obtain aluminum sol; mix ethanol, tetraethyl orthosilicate, and water in a molar ratio of 4:4:3, use hydrochloric acid to adjust the pH value to 2, and stir for 0.5 hour to obtain silica sol; mix aluminum sol, silica sol, and 1,2-propylene oxide to obtain mullite precursor sol; wherein the molar ratio of tetraethyl orthosilicate, aluminum chloride hexahydrate, and 1,2-propylene oxide is 1:3:9;
[0040] Step 3: Disperse 0.4 g of yttrium trioxide powder in 20 g of anhydrous ethanol, add 0.2 g of sodium dodecylbenzene sulfonate to obtain dispersion A; stir and dissolve 2.92 g of lanthanum nitrate (0.009 mol) in 30 g of deionized water, add 0.326 g of cerium nitrate (0.001 mol), stir for 45 min, then add 50 g of trisodium phosphate solution dropwise while stirring, continue stirring for 30 min to form dispersion B; mix dispersion A and dispersion B in a mass ratio of 1:1.5, hydrothermally react at 180°C for 24 h, wash with ethanol and water several times, dry, and calcine at 500°C for 2 h to obtain a composite powder;
[0041] Step 4: Mix and stir 5% composite powder and 95% mullite precursor sol to obtain a mixed slurry, apply the mixed slurry on the surface of the primary finished product with a coating thickness of 5 μm, and calcine at 1200° C. for 5 hours to obtain a high-temperature resistant silicon carbide heating element.
[0042] Example 4
[0043] Step 1: 80% silicon carbide powder, 10% silicon carbide fiber, 5% graphite, 2% metal silicon powder and 3% binder are mixed evenly; the mixture is pressed into shape to obtain a silicon carbide electric heating element blank; water-cooled for 10 minutes, biscuit-fired and baked the blank under vacuum, the biscuit temperature is 1100°C, the biscuit time is 15 minutes, and the blank is baked at 1650°C to obtain a primary finished product;
[0044] Step 2: Mix water, ethanol, and aluminum chloride hexahydrate in a molar ratio of 12:3:1, add hydrochloric acid to adjust the pH value to 3, and stir the reaction at 50°C for 1 hour to obtain aluminum sol; mix ethanol, tetraethyl orthosilicate, and water in a molar ratio of 4:4:3, use hydrochloric acid to adjust the pH value to 3, and stir for 0.5 hour to obtain silica sol; mix aluminum sol, silica sol, and 1,2-propylene oxide to obtain mullite precursor sol; wherein the molar ratio of tetraethyl orthosilicate, aluminum chloride hexahydrate, and 1,2-propylene oxide is 1:3:9;
[0045] Step 3: Disperse 0.4 g of yttrium trioxide powder in 20 g of anhydrous ethanol, add 0.2 g of sodium dodecylbenzene sulfonate to obtain dispersion A; stir and dissolve 2.92 g of lanthanum nitrate (0.009 mol) in 30 g of deionized water, add 0.326 g of cerium nitrate (0.001 mol), stir for 30 min, then add 50 g of trisodium phosphate solution dropwise while stirring, continue stirring for 30 min to form dispersion B; mix dispersion A and dispersion B in a mass ratio of 1:1.5, hydrothermally react at 180°C for 24 h, wash with ethanol and water several times, dry, and calcine at 400°C for 3 h to obtain a composite powder;
[0046] Step 4: Mix and stir 5% composite powder and 95% mullite precursor sol to obtain a mixed slurry, apply the mixed slurry on the surface of the primary finished product with a coating thickness of 5 μm, and calcine at 1200° C. for 3 hours to obtain a high-temperature resistant silicon carbide heating element.
[0047] Example 5
[0048] Step 1: 80% silicon carbide powder, 10% silicon carbide fiber, 5% graphite, 2% metal silicon powder and 3% binder are mixed evenly; the mixture is pressed into shape to obtain a silicon carbide electric heating element blank; water-cooled for 10 minutes, biscuit-fired and baked the blank under vacuum, the biscuit temperature is 1200°C, the biscuit time is 25 minutes, and baked at 1500°C to obtain a primary finished product;
[0049] Step 2: Mix water, ethanol, and aluminum chloride hexahydrate in a molar ratio of 12:3:1, add hydrochloric acid to adjust the pH value to 3, and stir the reaction at 60°C for 1 hour to obtain aluminum sol; mix ethanol, tetraethyl orthosilicate, and water in a molar ratio of 4:4:3, use hydrochloric acid to adjust the pH value to 2, and stir for 0.5 hour to obtain silica sol; mix aluminum sol, silica sol, and 1,2-propylene oxide to obtain mullite precursor sol; wherein the molar ratio of tetraethyl orthosilicate, aluminum chloride hexahydrate, and 1,2-propylene oxide is 1:3:9;
[0050] Step 3: Disperse 0.4 g of yttrium trioxide powder in 20 g of anhydrous ethanol, add 0.2 g of sodium dodecylbenzene sulfonate to obtain dispersion A; stir and dissolve 2.92 g of lanthanum nitrate (0.009 mol) in 30 g of deionized water, add 0.326 g of cerium nitrate (0.001 mol), stir for 30 min, then add 50 g of trisodium phosphate solution dropwise while stirring, continue stirring for 30 min to form dispersion B; mix dispersion A and dispersion B in a mass ratio of 1:1.5, hydrothermally react at 180°C for 24 h, wash with ethanol and water several times, dry, and calcine at 450°C for 3 h to obtain a composite powder;
[0051] Step 4: Mix and stir 5% composite powder and 95% mullite precursor sol to obtain a mixed slurry, apply the mixed slurry on the surface of the primary finished product with a coating thickness of 5 μm, and calcine at 1400° C. for 4.5 hours to obtain a high-temperature resistant silicon carbide heating element.
[0052] Example 6
[0053] Step 1: 80% silicon carbide powder, 10% silicon carbide fiber, 5% graphite, 2% metal silicon powder and 3% binder are mixed evenly; the mixture is pressed into shape to obtain a silicon carbide electric heating element blank; water-cooled for 15 minutes, biscuit-fired and baked the blank under vacuum, the biscuit temperature is 1300°C, the biscuit time is 15 minutes, and baked at 1800°C to obtain a primary finished product;
[0054] Step 2: Mix water, ethanol and aluminum chloride hexahydrate in a molar ratio of 12:3:1, add hydrochloric acid to adjust the pH value to 3, and stir the reaction at 65°C for 2 hours to obtain aluminum sol; mix ethanol, tetraethyl orthosilicate and water in a molar ratio of 4:4:3, use hydrochloric acid to adjust the pH value to 3, and stir for 1 hour to obtain silica sol; mix aluminum sol, silica sol and 1,2-propylene oxide to obtain mullite precursor sol; wherein the molar ratio of tetraethyl orthosilicate, aluminum chloride hexahydrate and 1,2-propylene oxide is 1:3:9;
[0055] Step 3: Disperse 0.4 g of yttrium trioxide powder in 20 g of anhydrous ethanol, add 0.2 g of sodium dodecylbenzene sulfonate to obtain dispersion A; stir and dissolve 2.92 g of lanthanum nitrate (0.009 mol) in 30 g of deionized water, add 0.326 g of cerium nitrate (0.001 mol), stir for 60 min, then add 50 g of trisodium phosphate solution dropwise while stirring, continue stirring for 30 min to form dispersion B; mix dispersion A and dispersion B in a mass ratio of 1:1.5, hydrothermally react at 180°C for 24 h, wash with ethanol and water several times, dry, and calcine at 500°C for 3 h to obtain a composite powder;
[0056] Step 4: Mix and stir 5% composite powder and 95% mullite precursor sol to obtain a mixed slurry, apply the mixed slurry on the surface of the primary finished product with a coating thickness of 5 μm, and calcine at 1500° C. for 5 hours to obtain a high-temperature resistant silicon carbide heating element.
[0057] Comparative Example 1
[0058] No mixed slurry was used for coating, and the other parameters were the same as those in Example 1.
[0059] Step 1: Evenly mix 80% silicon carbide powder, 10% silicon carbide fiber, 5% graphite, 2% metal silicon powder and 3% binder; press the mixture into a shape to obtain a silicon carbide electric heating element blank; water cool for 10 minutes, biscuit and bake the blank under vacuum, the biscuit temperature is 800°C, the biscuit time is 30 minutes, and bake at 1500°C to obtain a high temperature resistant silicon carbide electric heating element.
[0060] Comparative Example 2
[0061] No composite powder was added, and other parameters were the same as those in Example 2.
[0062] Step 1: 80% silicon carbide powder, 10% silicon carbide fiber, 5% graphite, 2% metal silicon powder and 3% binder are mixed evenly; the mixture is pressed into shape to obtain a silicon carbide electric heating element blank; water-cooled for 12 minutes, biscuit-fired and baked the blank under vacuum, the biscuit temperature is 900°C, the biscuit time is 20 minutes, and the blank is baked at 1550°C to obtain a primary finished product;
[0063] Step 2: Mix water, ethanol and aluminum chloride hexahydrate in a molar ratio of 12:3:1, add hydrochloric acid to adjust the pH value to 2, and stir the reaction at 55°C for 2 hours to obtain aluminum sol; mix ethanol, tetraethyl orthosilicate and water in a molar ratio of 4:4:3, use hydrochloric acid to adjust the pH value to 2, and stir for 1 hour to obtain silica sol; mix aluminum sol, silica sol and 1,2-propylene oxide to obtain mullite precursor sol; wherein the molar ratio of tetraethyl orthosilicate, aluminum chloride hexahydrate and 1,2-propylene oxide is 1:3:9;
[0064] Step 3: The mullite precursor sol is coated on the surface of the primary finished product with a coating thickness of 5 μm, and calcined at 1200° C. for 4 hours to obtain a high-temperature resistant silicon carbide electric heating element.
[0065] Comparative Example 3
[0066] The amount of composite powder was increased, and the other parameters were the same as those in Example 3.
[0067] Step 1: 80% silicon carbide powder, 10% silicon carbide fiber, 5% graphite, 2% metal silicon powder and 3% binder are mixed evenly; the mixture is pressed into shape to obtain a silicon carbide electric heating element blank; water-cooled for 20 minutes, biscuit-fired and baked the blank under vacuum conditions, the biscuit temperature is 1000°C, the biscuit time is 20 minutes, and baked at 1600°C to obtain a primary finished product;
[0068] Step 2: Mix water, ethanol, and aluminum chloride hexahydrate in a molar ratio of 12:3:1, add hydrochloric acid to adjust the pH value to 2, and stir the reaction at 65°C for 1 hour to obtain aluminum sol; mix ethanol, tetraethyl orthosilicate, and water in a molar ratio of 4:4:3, use hydrochloric acid to adjust the pH value to 2, and stir for 0.5 hour to obtain silica sol; mix aluminum sol, silica sol, and 1,2-propylene oxide to obtain mullite precursor sol; wherein the molar ratio of tetraethyl orthosilicate, aluminum chloride hexahydrate, and 1,2-propylene oxide is 1:3:9;
[0069] Step 3: Disperse 0.4 g of yttrium trioxide powder in 20 g of anhydrous ethanol, add 0.2 g of sodium dodecylbenzene sulfonate to obtain dispersion A; stir and dissolve 2.92 g of lanthanum nitrate (0.009 mol) in 30 g of deionized water, add 0.326 g of cerium nitrate (0.001 mol), stir for 45 min, then add 50 g of trisodium phosphate solution dropwise while stirring, continue stirring for 30 min to form dispersion B; mix dispersion A and dispersion B in a mass ratio of 1:1.5, hydrothermally react at 180°C for 24 h, wash with ethanol and water several times, dry, and calcine at 500°C for 2 h to obtain a composite powder;
[0070] Step 4: Mix and stir 15% of the composite powder and 85% of the mullite precursor sol to obtain a mixed slurry, apply the mixed slurry on the surface of the primary finished product with a coating thickness of 5 μm, and calcine at 1200° C. for 5 hours to obtain a high-temperature resistant silicon carbide heating element.
[0071] experiment:
[0072] The samples were placed in air at 1500°C for 200 hours of aging, and the resistance change rate and flexural strength retention rate before and after aging were tested; where:
[0073] Resistance change rate = (resistance after aging - resistance before aging) / resistance before aging × 100%;
[0074] Flexural strength retention rate = flexural strength after aging / flexural strength before aging × 100%;
[0075] The oxidation weight gain rate under constant temperature oxidation state is used to describe the high temperature oxidation resistance of the coating. The cyclic oxidation method is used. The sintered sample is placed in a resistance furnace, heated to 1200°C, kept warm for 24 hours, and then taken out for air cooling. The mass of the sample is recorded with a precision electronic balance (accuracy of 0.01 mg). The oxidation weight gain rate G = (sample weight after oxidation - sample weight before oxidation) / sample weight before oxidation × 100%.
[0076] Example Resistance change rate / % Flexural strength retention rate / % Oxidation weight gain rate / % Example 1 9.9 92.4 0.095 Example 2 10.2 92.6 0.092 Example 3 10.0 91.3 0.096 Example 4 9.8 90.6 0.093 Example 5 9.9 90.9 0.094 Example 6 10.1 91.7 0.098 Comparative Example 1 20.4 80.7 0.198 Comparative Example 2 14.5 86.4 0.136 Comparative Example 3 17.8 84.3 0.154
[0077] in conclusion:
[0078] The silicon carbide electric heating element prepared by the present invention has good high temperature resistance. After aging for 200 hours at a high temperature of 1500°C, the resistivity changes slightly and the flexural strength retention rate reaches more than 90%. In the thermal oxidation test, the oxidation weight gain rate is less than 0.1%, and it has a good anti-oxidation effect.
[0079] The data of Example 1 and Comparative Example 1 show that the anti-aging resistivity of the silicon carbide heating element after coating with the mixed slurry changes less, the flexural strength retention rate is high, and it has good antioxidant effect. The data of Example 2 and Comparative Example 2 show that in Example 2, after adding the composite powder to the mullite precursor sol, the prepared silicon carbide heating element has better performance. This is mainly because the composite powder has a shell-core structure, the outer shell is lanthanum cerate, and the inner core is yttrium trioxide. When the mixed slurry is coated on the surface of the heating element and calcined, the mullite precursor sol will first generate a mullite layer, which adheres to the surface of the silicon carbide heating element. As the calcination time increases, a large number of cracks will appear in the shell layer of lanthanum cerate, releasing the inner core. Yttrium trioxide in the part; Yttrium trioxide, as a sintering aid, forms a low-temperature eutectic phase after contacting mullite at high temperature, which reduces the temperature of liquid phase generation, so that the liquid phase participates in the sintering process that was originally dominated by solid phase reaction. Under the action of the capillary force and surface tension of the liquid phase, the solid phase grains are rearranged, making the surface coating densified, thereby effectively blocking the silicon carbide electric heating element from reacting with external oxidizing factors. Therefore, the silicon carbide electric heating element prepared in Example 2 has better high-temperature electric heating performance. The data of Example 3 and Comparative Example 3 show that excessive addition of composite powder will also affect the performance of the final silicon carbide electric heating element. As the amount of composite powder increases, the content of lanthanum cerate also increases. Under the action of high temperature, lanthanum cerate continuously splits into fragments, and a large number of voids appear inside the coating, which seriously reduces the density of the coating. In actual use, oxygen will penetrate into the coating through the voids, and after contacting the body of the electric heating element, an oxidation reaction occurs, resulting in performance degradation.
[0080] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high temperature resistant silicon carbide electric heating element, characterized in that: The following steps are involved: Step 1: Evenly mix silicon carbide powder, silicon carbide fiber, graphite, metal silicon powder and a binder; press the mixture into a shape to obtain a silicon carbide electric heating element blank; water-cool, biscuit-sinter, and roast the blank to obtain a primary product; Step 2: Mix water, ethanol and aluminum chloride hexahydrate, add hydrochloric acid to adjust the pH value to 2-3, stir and react in a water bath to obtain aluminum sol; mix ethanol, tetraethyl orthosilicate and water, use hydrochloric acid to adjust the pH value to 2-3, stir and react to obtain silica sol; mix the aluminum sol and silica sol, add 1,2-propylene oxide to obtain a mullite precursor sol; Step 3: Dispersing yttrium trioxide powder in anhydrous ethanol, adding sodium dodecylbenzene sulfonate to obtain dispersion A; stirring and dissolving lanthanum nitrate in deionized water, adding cerium nitrate, stirring, and then adding trisodium phosphate solution dropwise while stirring, and continuing to stir to form dispersion B; mixing dispersion A and dispersion B to prepare composite powder; Step 4: Mix and stir the composite powder and the mullite precursor sol to obtain a mixed slurry, apply the mixed slurry on the surface of the primary finished product, and calcine to obtain a high-temperature resistant silicon carbide electric heating element.
2. The method for preparing a high temperature resistant silicon carbide electric heating element according to claim 1, characterized in that: In step 1, the amount of each component, by weight percentage, is 70-80% silicon carbide powder, 5-20% silicon carbide fiber, 3-5% graphite, 1-2% metallic silicon powder, and 0.5-3% binder.
3. The method for preparing a high temperature resistant silicon carbide electric heating element according to claim 1, characterized in that: In step 2, the molar ratio of water, ethanol and aluminum chloride hexahydrate in the aluminum sol is (10-14): (2-3): 1; and the molar ratio of ethanol, tetraethyl orthosilicate and water in the silica sol is (3-4): 4: (3-4).
4. The method for preparing a high temperature resistant silicon carbide electric heating element according to claim 1, characterized in that: In step 2, the water bath temperature is 50-65° C., the stirring reaction time is 1-2 h, and the silica sol stirring reaction time is 0.5-1 h.
5. The method for preparing a high temperature resistant silicon carbide electric heating element according to claim 1, characterized in that: In step 2, in the mullite precursor sol, the molar ratio of tetraethyl orthosilicate, aluminum chloride hexahydrate and 1,2-propylene oxide is 1:3:(6-9).
6. The method for preparing a high temperature resistant silicon carbide electric heating element according to claim 1, characterized in that: In step 3, the amount of each component in dispersion A, by weight, is 0.3-0.5 parts of yttrium trioxide powder, 10-20 parts of anhydrous ethanol, and 0.1-0.2 parts of sodium dodecylbenzene sulfonate; the amount of each component in dispersion B, by weight, is 2-3 parts of lanthanum nitrate, 30-40 parts of deionized water, 0.2-0.4 parts of cerium nitrate, and 50-60 parts of trisodium phosphate solution.
7. The method for preparing a high temperature resistant silicon carbide electric heating element according to claim 1, characterized in that: In step 3, the preparation method of the composite powder is to mix dispersion A and dispersion B in a mass ratio of 1: (1 to 1.5), hydrothermally react at 160 to 200° C. for 18 to 24 hours, wash with ethanol and water several times, dry, and calcine at 400 to 500° C. for 2 to 3 hours to obtain a composite powder.
8. The method for preparing a high temperature resistant silicon carbide electric heating element according to claim 1, characterized in that: In step 4, the mixed slurry contains, by weight percentage, 5 to 10% of the composite powder and 90 to 95% of the mullite precursor sol.
9. The method for preparing a high temperature resistant silicon carbide electric heating element according to claim 1, characterized in that: In step 4, the calcination temperature is 1200-1500° C., and the calcination time is 3-5 hours. 10 . A high temperature resistant silicon carbide electric heating element prepared by the method for preparing a high temperature resistant silicon carbide electric heating element according to any one of claims 1 to 9.
Citation Information
Patent Citations
Three-dimensional carbon fiber fabric reinforced mullite ceramic and preparation method thereof
CN102126868A
Preparation method of mullite oxidation resistant coating
CN105000917A
Preparation method and application of perovskite type high-entropy high-emissivity ceramic coating film plating liquid
CN114573345A
Production of silicon carbide porous body
JP1997268085A
Refractory for spraying repair
JP1999199338A
Cited By
New energy automobile tire sidewall rubber and preparation method thereof
CN122465234A